Primula longipes subsp. bayburtensis Sefali, Yapar & Demir (Primulaceae): A new taxon from north-eastern Anatolia, Türkiye - Abdurrahman Sefalı; Yakup Yapar; İbrahim Demir; Bayram Yurtvermez; Ali Murat Keser (PhytoKeys)
The new taxon, Primula longipes subsp. bayburtensis Sefali, Yapar & Demir, subsp. nov. (Primulaceae) is described and illustrated from Bayburt Province, Türkiye. It is morphologically assigned to Primula sect. Crystallophlomis based on its long scapes, lanceolate and denticulate leaf with long petiole and hairless habit, fruits longer than calyx and covered by farina on the scape. This new taxon is similar to Primula longipes and P. nivalis subsp. turkestanica; it can also be easily distinguished by its calyx divided ratio, thurm flowers (unwidened corolla tube shape and length) and capsules (length) futures.